2023
DOI: 10.3389/fphar.2023.1185076
|View full text |Cite
|
Sign up to set email alerts
|

One stone two birds: anti-inflammatory bronchodilators as a potential pharmacological strategy for COVID-19

Abstract: The ongoing Coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has imposed a huge threat to public health across the world. While vaccinations are essential for reducing virus transmission and attenuating disease severity, the nature of high mutation rate of SARS-CoV-2 renders vaccines less effective, urging quick development of effective therapies for COVID-19 disease. However, developing novel drugs remains extremely challenging due to the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…It has also been reported that corticosteroids, including prednisone, are effective in reducing mortality in COVID-19 patients within their therapeutic window [ 27 ], or reduce hospitalization times, like budesinode [ 32 ]. Some studies suggest that formoterol could be used to improve lung function and assist symptom control in COVID-19 patients [ 33 ] however, the available evidence does not suggest any significant interaction between formoterol and COVID-19 [ 34 ]. A recent study suggested that olmesartan could alleviate renal fibrosis induced by SARS-CoV-2 envelope protein by regulating HMGB1 release and autophagic degradation of TGF-β1 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that corticosteroids, including prednisone, are effective in reducing mortality in COVID-19 patients within their therapeutic window [ 27 ], or reduce hospitalization times, like budesinode [ 32 ]. Some studies suggest that formoterol could be used to improve lung function and assist symptom control in COVID-19 patients [ 33 ] however, the available evidence does not suggest any significant interaction between formoterol and COVID-19 [ 34 ]. A recent study suggested that olmesartan could alleviate renal fibrosis induced by SARS-CoV-2 envelope protein by regulating HMGB1 release and autophagic degradation of TGF-β1 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%